(untitled) (Revista Rupturas, 2022)
This essay shows the relationship between the meat industry and inequality. To achieve this purpose, a historical-philosophical journey is made to understand the unequal world in which we live. Then, it is exposed how the consumption of meat contributes to reinforcing this inequality and, finally, the crime against the ecosocialist is reviewed as a clear example that the meat industry brings more destruction and fewer opportunities.